HUBUNGAN ANTARA TINGKAT RELIGIUSITAS DENGAN PERILAKU SEKS BEBAS PADA REMAJA MESJID DI DESA CIKUNGKURAK BANDUNG - Bobby G. Hidayatuddin; Ulfiah Ulfiah; Ening Ningsih (Psympathic : Jurnal Ilmiah Psikologi, 2012)
This research based on phenomena of teenagers who actively join mosque activity but often do free sex such as exchanging partners, paying whore both from the steet and prostitution. They know what they do is a sin but they said that they can not control themselves. It can be said that subjects in this problem have high religious level and high free sex behaviours. This quantitative research used correlational methodology. Population are 120 teenagers around 4 mosques who actively join mosque activity in Cikungkurak Bandung. Correlation between two variables analyzed using statistical correlation Rank Spearman. Result found coefficient correlation between religiousity and free sex behaviour is -0,187 with sifnificant level is 0,030 and α= 0,05. Since significant level is less than α, so Ho is rejected. Therefore, it is concluded that there is negative correlation between religiousity and free sex behaviours.